Konstruksi Epistemologis dalam Pengembangan Berpikir Kritis Siswa Sekolah Dasar - Satria, Liza; Auji, Nurizam; Saragi, Daulat (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the effectiveness of epistemology-based learning in improving the understanding of science concepts among fifth-grade students at PAB 27 Tanjung Mulia Private Elementary School. The research uses a quasi-experimental method with a pretest-posttest control group design involving 52 students, consisting of 26 students in the experimental class and 26 students in the control class. The experimental class received epistemology-based learning involving activities of little scientists such as observing phenomena, formulating questions, constructing hypotheses, conducting experiments, and drawing evidence-based conclusions, while the control class received conventional learning. Data were collected thru written tests, observation of learning activities, and documentation, then analyzed using normality tests, homogeneity tests, independent sample t-tests, and N-Gain calculations. The research results showed that the average Posttest score of the experimental class was higher than that of the control class (81.5 vs 68.7), with an average N-Gain of 0.61 (medium-high) in the experimental class and 0.32 (low-medium) in the control class. Statistical analysis shows a significant difference between the two groups (p < 0.05). These findings indicate that epistemology-based learning significantly enhances students' understanding of science concepts, critical thinking skills, as well as their motivation and active participation. This research suggests the integration of epistemological principles in science learning practices in elementary schools to strengthen students' conceptual understanding and 21st-century skills.